Adenosine A(2B) receptors induce proliferation, invasion and activation of cAMP response element binding protein (CREB) in trophoblast cells - Darashchonak, Natallia (BioMed Central, 2014)
BACKGROUND: Placental hypoxia is a result of abnormal and shallow trophoblast invasion and involved in the pathophysiology of preeclampsia. Hypoxia increases extracellular adenosine levels and plays an important role in the regulation of angiogenesis, proliferation, vascular tone, endothelial permeability and inflammation. It was shown that adenosine concentrations are higher in preeclamptic patients. We tested the hypothesis that hypoxia and A(2B) adenosine receptor activation influence cyclic adenosine monophosphate (cAMP) production, proliferation, invasion and cAMP-PKA-CREB signaling in trophoblast cells (HTR-8/SVneo). METHODS: HTR-8/SVneo and human uterine microvascular endothelial cells (HUtMVEC) were used as model for experiments. We employed a cAMP assay, invasion assay, proliferation, RT-PCR and Western Blot. Statistical analyses were performed with ANOVA, Kruskal-Wallis-, Wilcoxon signed rank- or Mann–Whitney Test, as appropriate. RESULTS: Hypoxia (2% O(2)) in comparison to normoxia (21% O(2)) led to increased A(2B) mRNA levels (1.21 ± 0.06 fold, 1 h 2% O(2); 1.66 ± 0.2 fold, 4 h 2% O(2) and 1.2 ± 0.04 fold, 24 h 2% O(2)). A(2B) adenosine receptor activation (NECA) stimulated trophoblast proliferation at 2% O(2) (1.27 ± 0.06 fold) and 8% O(2) (1.17 ± 0.07 fold) after 24 h and at 2% O(2) (1.22 ± 0.05 fold), 8% O(2) (1.23 ± 0.09 fold) and 21% O(2) (1.15 ± 0.04 fold) after 48 h of incubation. Trophoblast invasion into an endothelial monolayer was significantly expanded by activation of the receptor (NECA) at 8% O(2) (1.20 ± 0.07 fold) and 21% O(2) (1.22 ± 0.006 fold). A(2B) adenosine receptor stimulation (NECA) additionally led to increased CREB phosphorylation in trophoblast cells at 2% O(2) (2.13 ± 0.45 fold), 8% O(2) (1.55 ± 0.13 fold) and 21% O(2) (1.71 ± 0.34 fold). Blocking of CREB signaling resulted in reduced proliferation and CREB phosphorylation. CONCLUSION: These data expand the recent knowledge regarding the role of adenosine receptor A(2B) in human placental development, and may provide insight in mechanisms associated with pregnancy complications linked to impaired trophoblast invasion such as preeclampsia.